Demographic profile of pediatric malignancies in Himachal Pradesh - Anupam Badhan; Parveen Bhardwaj; Vijay Yadav; Neelam Grover; Rajeev Kumar Seem (Indian Journal of Medical and Paediatric Oncology)
Context: Pediatric malignancy is on the rise worldwide, and it is imperative to know the profile of pediatric malignancy in different geographical areas so as to formulate effective strategy to its control. As there are no data from this part, especially the Himalayan region of North India, the present study was planned. Aims: The aims of this study were to study the pattern and demographic profile of pediatric malignancies at a tertiary care teaching hospital in Himachal Pradesh. Settings and Design: This was a hospital-based, prospective, nonrandomized, observational study. Subjects and Methods: Pattern and demographic profile of clinically suspected malignancies in children and adolescents (0–18 years) over a period of 1 year from June 2012 to May 2013 in the Department of Pediatrics and Radiotherapy. Statistical Analysis Used: Data were analyzed statistically using Epi Info software for all ratios and proportions. Results: A total of 31 children were diagnosed to have malignancy, which accounted for 0.86% of total admissions with a male-to-female ratio of 1.58:1.The three most common childhood malignancies were leukemia (29.03%), central nervous system (CNS) tumors (25.80%), and lymphoma (19.35%), and these were followed by Wilm's tumor and hepatoblastoma, each accounting for 06.45% of total childhood malignancies. Hematological malignancies accounted for 48.38% and nonhematological malignancies for 51.62% of all the malignancies. Acute lymphoblastic leukemia was the most common hematological malignancy noted in 22.58%, followed equally by Hodgkin's disease and non-Hodgkin's lymphoma (20% of total hematological malignancies). Among nonhematological malignancies, CNS malignancies were the most common. In the age group of 0–5 years, all cases of neuroblastoma, yolk sac tumor, and ovarian tumor and 50% cases of hepatoblastoma and Wilm's tumor were seen. In the age group of 5–10 years, leukemia (44.44%) was the most common malignancy followed by lymphoma (33.33%). In 14–18 years, CNS malignancies (50%) were the most common malignancies followed by lymphoma (33.33%). Conclusions: Hematological malignancies are the most common malignancies in the pediatric age group, and acute leukemia was the single most common pediatric malignancy, and CNS malignancies were the most common nonhematological malignancies.